Wait-and-See Policy for a Small Pancreatic Schwannoma Diagnosed With Endoscopic Ultrasound With Fine-Needle Aspiration. Issue 7 (July 2019) - Bruno, Mauro; Maletta, Francesca; Gaia, Silvia; Venezia, Ludovica; Cortegoso Valdivia, Pablo; Saracco, Giorgio Maria; De Angelis, Claudio Giovanni
Abstract : ABSTRACT: Pancreatic schwannomas are very rare tumors, usually diagnosed incidentally after surgery. In literature, only 17 patients underwent endoscopic ultrasound (EUS) with fine-needle aspiration and diagnosis was reached only in 9 subjects. We report the case of a woman in whom a computed tomography revealed a mass in the uncinate process of the pancreas. EUS–fine-needle aspiration demonstrated a 1.3 × 1.1 cm hypoechoic lesion, cytology revealed sheets of spindle cells, and immunocytochemistry led to the diagnosis of schwannoma. Relying on EUS features and on the low proliferation index, a follow-up program was set. Four years later, the patient is asymptomatic and the mass is unchanged.